2011
DOI: 10.1159/000324653
|View full text |Cite
|
Sign up to set email alerts
|

The Syndrome of Inappropriate Antidiuresis: Pathophysiology, Clinical Management and New Therapeutic Options

Abstract: Hyponatremia is a marker of different underlying diseases and it can be a cause of morbidity itself; this implies the importance of a correct approach to the problem. The syndrome of inappropriate antidiuresis (SIAD) is one of the most common causes of hyponatremia: it is a disorder of sodium and water balance characterized by urinary dilution impairment and hypotonic hyponatremia, in the absence of renal disease or any identifiable non-osmotic stimulus able to induce antidiuretic hormone (ADH) release; accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
101
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 143 publications
0
101
0
6
Order By: Relevance
“…9,10 The syndrome of the inappropriate release of antidiuretic hormone (SIADH) is additionally a predominant cause of hyponatremia, with a prevalence reported as high as 35% in hospitalized patients. 11 Hyponatremia is not only widespread, but also an independent predictor of mortality. In a retrospective cohort analysis, Waikar et al reported that in comparison to patients who were normonatremic, patients with serum sodium concentrations <135 mEq/L had a risk of in-hospital mortality as high as 47%, and that this risk doubled for patients with serum sodium concentrations between 125 and 129 mEq/L.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The syndrome of the inappropriate release of antidiuretic hormone (SIADH) is additionally a predominant cause of hyponatremia, with a prevalence reported as high as 35% in hospitalized patients. 11 Hyponatremia is not only widespread, but also an independent predictor of mortality. In a retrospective cohort analysis, Waikar et al reported that in comparison to patients who were normonatremic, patients with serum sodium concentrations <135 mEq/L had a risk of in-hospital mortality as high as 47%, and that this risk doubled for patients with serum sodium concentrations between 125 and 129 mEq/L.…”
Section: Discussionmentioning
confidence: 99%
“…The case presented in this paper could correspond to SIADH type C described above [13,14], because the patient periodically showed a progressive increase in plasma vasopressin that closely correlated with increased plasma sodium, and at other times the patient showed normal or decreased levels of VAS that corresponded to normal or decreased levels of plasma sodium.…”
Section: Discussionmentioning
confidence: 68%
“…The Syndrome of Inappropriate Antidiuretic Hormone Secretion or Syndrome of Inappropriate Antidiuresis, is apparently induced by an extensive range of diseases, drugs, and/or injuries and is divisible into 3 kinds of abnormal vasopressin (VAS) release during hypertonic saline infusion [13]: type A, elevated, inconsistent fluctuations unrelated to increases in plasma sodium; type B, a slow regular release, that is also unaltered by increases in plasma sodium; type C, a quick progressive increase in plasma VAS that closely correlates with plasma sodium as it rises towards the normal range; there is also another kind, type D, that appears in a low percentage of patients, where there is no demonstrable defect in the osmoregulation of AVP and the cause of inappropriate antidiuresis is imprecise [13,14]. The case presented in this paper could correspond to SIADH type C described above [13,14], because the patient periodically showed a progressive increase in plasma vasopressin that closely correlated with increased plasma sodium, and at other times the patient showed normal or decreased levels of VAS that corresponded to normal or decreased levels of plasma sodium.…”
Section: Discussionmentioning
confidence: 99%
“…We determined the dog was euvolemic based on physical examination findings and absence of other clinical signs (eg, vomiting, diarrhea) or concurrent multiorgan damage. In human patients, the diagnosis of SIADH must include decreased plasma osmolality (<274 mOsm/kg), increased urinary osmolality (>100 mOsm/kg during hypotonicity), increased urinary sodium concentration (>40 mmol/L), euvolemia, normal thyroid and adrenal function, and no recent use of diuretic agents 2, 16. In this patient, persistent hyponatremia, plasma hypoosmolality, and increased urine osmolality were documented, with normal serum cortisol concentration.…”
mentioning
confidence: 77%